2014
DOI: 10.1002/poc.3392
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of reversible disproportionation–comproportionation in redox triad oxoammonium cations – nitroxyl radicals – hydroxylamines

Abstract: Kinetics and equilibrium of the acid-catalyzed disproportionation of cyclic nitroxyl radicals R 2 NO• to oxoammonium cations R 2 NO + and hydroxylamines R 2 NOH is defined by redox and acid-base properties of these compounds. In a recent work (J. Phys. Org. Chem. 2014, 27, 114-120), we showed that the kinetic stability of R 2 NO• in acidic media depends on the basicity of the nitroxyl group. Here, we examined the kinetics of the reverse comproportionation reaction of R 2 NO + and R 2 NOH to R 2 NO• and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The studies of the redox characteristics of NR by the method of cyclic voltammetry had demonstrated that, in many solvents (H 2 O, MeCN, DMF), electron transfer in the pair of NR–OC is characterized by a high degree of reversibility. , However, our experiments and literature data showed the presence of an irreversible process in DMSO, as evidenced by a decrease in the amplitude of the current–voltage curves during repeated oxidation–reduction cycles. Since the NR solutions in DMSO are stored unchanged for long time periods exceeding weeks, the irreversibility mentioned can only be caused by the reaction of DMSO with OC.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The studies of the redox characteristics of NR by the method of cyclic voltammetry had demonstrated that, in many solvents (H 2 O, MeCN, DMF), electron transfer in the pair of NR–OC is characterized by a high degree of reversibility. , However, our experiments and literature data showed the presence of an irreversible process in DMSO, as evidenced by a decrease in the amplitude of the current–voltage curves during repeated oxidation–reduction cycles. Since the NR solutions in DMSO are stored unchanged for long time periods exceeding weeks, the irreversibility mentioned can only be caused by the reaction of DMSO with OC.…”
Section: Introductionmentioning
confidence: 57%
“…The synthesis of oxoammonium perchlorates 1 was carried out according to the methods described elsewhere. 18 The purity of salts 1, checked by iodometric titration and/or by the 1 H NMR, was 98 ± 2%. MeCN was purified by distillation from P 2 O 5 and stored over 3 Å molecular sieves.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…To gain further insight into the observed trends regarding the solvent‐, metal‐ion‐, and temperature‐dependent disproportionation behavior of {[M](PF 6 )} n (M=Ni ( n =2), Pd ( n =1), and Pt ( n =1)), we conducted electrochemical studies as the redox potential serves as an indicator of the stability of each species . Figure shows the cyclic voltammograms of [M] (M=Ni, Pd, and Pt) recorded in CH 2 Cl 2 and in DMF containing 0.1 m (TBA)(PF 6 ) as the supporting electrolyte (see Figures S22 and S23 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of PaNDA label 1 , carboxy TEMPO 5 was quantitatively transformed into hydroxylammonium salt 6 by making use of the acid‐dependent redox triad of a nitroxyl radical, an oxoammonium cation, and hydroxylamine (Scheme A) . Conveniently, the carboxylic acid is simultaneously protected under these conditions.…”
Section: Figurementioning
confidence: 99%